Embrace a circular economy during celebrations - Ong, Hwai Chyuan *; Long, Chiau Ming *; Gew, Lai Ti * (Star Media Group Berhad, 2025)
The festivals of Chinese New Year, Thaipusam and Hari Raya will be observed in the coming months. With the future generation in mind, we must optimise the opportunity to enjoy celebrations while also taking care of the planet. Let's not take for granted the various waste or carbon footprints we produce as well as the resources we consume. One way to do this is by embracing the principles of the circular economy. In layman's terms, a circular economy is a system that minimises waste and maximises resource use – it is all about making the most of what we already have.